Plant chemical variation mediates soil bacterial community composition - Robert W. Buchkowski; Benedek Klára; Bálint János; Molnár Attila; Молнар Атілла; Felföldi Tamás; Fazakas Csaba; Schmitz Oswald J.; Balog Adalbert (Springer Nature, 2023)
Abstract. An important challenge in the study of ecosystem function is resolving how plant antiherbivore chemical defence expression may influence plant-associated microbes, and nutrient release. We report on a factorial experiment that explores a mechanism underlying this interplay using individuals of the perennial plant Tansy that vary genotypically in the chemical content of their antiherbivore defenses (chemotypes). We assessed to what extent soil and its associated microbial community versus chemotype-specific litter determined the composition of the soil microbial community. Microbial diversity profiles revealed sporadic effects of chemotype litter and soil combinations. Soil source and litter type both explained the microbial communities decomposing the litter with soil source having a more important effect. Some microbial taxa are related to particular chemotypes, and thus intra-specific chemical variation of a single plant chemotype can shape the litter microbial community. But we found that ultimately the effect of fresh litter inputs from a chemotype appeared to act secondary as a filter on the composition of the microbial community, with the primary factor being the existing microbial community in the soil.
Keywords: plant; soil bacterial community; soil